Using the “One Shot” Concept for Immediate Loading Implant Protocol in Edentulous Patient Rehabilitation with a Fixed Prosthesis: A 6-Year Follow-Up - Philippe Bousquet; Delphine Carayon; Jean-Cedric Durand (Case Reports in Dentistry)
Immediate-loaded implants with a fixed prosthesis are a viable option for the restoration of edentulous ridges. Several procedures now allow for the fabrication of immediate-loading provisional and definitive prostheses. However, this complex treatment is not accessible to all patients with budget restrictions. By using a unique master model with a single titanium framework prosthesis can simplify and shorten the treatment, as well as reduce costs. After surgical placement of implant fixtures, an interim prosthesis was fabricated using a laser-welded definitive titanium framework. The prosthesis was fitted intraorally following the immediate loading protocols. The master cast model used to fabricate interim prosthesis was conserved and subsequently used in modifying the final prosthesis. After the healing process and complete soft tissue stability, an impression was made to register the clearance between the gingiva and resin. The light silicone material was directly injected under the prosthesis screwed in the mouth. In the master cast model, the stone was eliminated between the implants and a new plaster was poured to modify the crest profile with the posthealing new shape. With this modified model, it is possible to rehabilitate the denture to the new gingival anatomy in 3 to 4 hours and, if necessary, the tooth rearrangement. This “one shot” concept combines the single definitive titanium welded framework and limited laboratory work with a unique master model thereby decreasing the cost and the time of treatment.